Exploring EFL Student Teachers’ Experiences on the Roles of Teacher Mentors during Teaching Practicum - Suhandra, Ika Rama; Ariawan, Soni (Journal of Languages and Language Teaching, 2023)
Teacher mentors play a crucial role in supporting and guiding student teachers during their teaching practicum. While the benefits of teaching practicum and mentorship are well-documented, this qualitative study aims to delve deeper into the experiences of five EFL student teachers to understand the role of teacher mentor during student teacher practicum. Through in-depth interviews, the research explores the perceptions of student teachers towards the practicum and mentorship. The results reveal that the role of teacher mentors is positively perceived by most of the students, because most of the mentors play a pivotal role in providing guidance and motivation, desiging a lesson plan and giving constructive feedback. However, some students experienced lack of guidance, support as well as constructive feedback from the teacher mentors. In general, the mentorship aspect is particularly valued, as it offers essential support and professional growth opportunities. However, amidst the positive experiences, the study also uncovers various challenges encountered by student teachers such as lack of class management skill, limited student engagement and active involvement in the learning process, inadequate facilities, limited technology or classroom space and lack of sufficient preparation.